Comparison of Mechanical and Macrostructural Behavior of TIG and Friction Stir Welded Dissimilar Aluminium Alloys SSM356-T6 and SSM6061-T6 - เมฆารัฐ อามีณา; เมืองจันทร์บุรี ประภาศ; สุธรรมานนท์ เสกสรร; เต๊ะยอ มูหามัด (Princess of Naradhiwas University Journal, 2018)
The objective of this research was to investigate the mechanical properties and macrostructural of dissimilar aluminium alloys SSM356-T6 and SSM6061-T6 jointed by different processes: TIG and Friction stir welding (FSW). Friction stir welding is a solid state welding. An aluminium alloys 4 mm thickness was used as based material for preparing butt joint welded and filler rod type of AA4043 was used as joining the plate. The result showed that the tensile properties of joints dissimilar aluminium alloys SSM356-T6 and SSM6061-T6 by FSW were superior to TIG welding.